2017
DOI: 10.1098/rsos.160963
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific but not sexually explicit: pupillary responses to dressed and naked adults

Abstract: Dilation of the pupils is an indicator of an observer's sexual interest in other people, but it remains unresolved whether this response is strengthened or diminished by sexually explicit material. To address this question, this study compared pupillary responses of heterosexual men and women to naked and dressed portraits of male and female adult film actors. Pupillary responses corresponded with observers' self-reported sexual orientation, such that dilation occurred during the viewing of opposite-sex people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In two experiments, they showed the greatest pupil response to images of women for both heterosexual men and heterosexual women. However, in a later study (Attard-Johnson & Bindemann, 2017) they reported that pupil dilation was commensurate with stated sexual interest and was unaffected by the erotic content of the image. Clearly, these results contradict (some) of the present results.…”
Section: Discussionmentioning
confidence: 89%
“…In two experiments, they showed the greatest pupil response to images of women for both heterosexual men and heterosexual women. However, in a later study (Attard-Johnson & Bindemann, 2017) they reported that pupil dilation was commensurate with stated sexual interest and was unaffected by the erotic content of the image. Clearly, these results contradict (some) of the present results.…”
Section: Discussionmentioning
confidence: 89%
“…In consumer science, various studies have reported increases in pupil size in response to stimuli and experiences that evoke strong interest and emotions in consumers, such as when consumers listen to music that they experience as enjoyable and emotion-evoking ( Laeng et al, 2016 ) or when viewing human faces ( Blackburn and Schirillo, 2012 ) or art that are experienced as aesthetically pleasant ( Johnson et al, 2010 ). Increases in pupil size also allow researchers to differentiate consumers based on their interests, for instance, pupillary increases in response to (erotic) images of female and male models correspond with the sexual orientation of observers ( Rieger and Savin-Williams, 2012 ; Attard-Johnson and Bindemann, 2017 ; Watts et al, 2017 ) and impulsive, but not non-impulsive, buyers display enhanced pupil dilation when they are presented with shopping scenes ( Serfas et al, 2014 ). Pupillary measures are thus useful to measure whether products, experiences or people evoke interest and emotional reactions and arousal in consumers.…”
Section: Physiological and Neuroscientific Measures Used In Consumer mentioning
confidence: 99%
“…This study further demonstrated pupillary dilation in response to viewing the chest and pelvic regions, suggesting that the participants were more aroused by these regions. Attard-Johnson and Bindemann (2017) found that when viewing clothed subjects, nude subjects, and nude subjects with both chest and genitals blurred, men viewed the faces longest for all three image types, but spent more time viewing the chest and pelvic region when the model was nude.…”
Section: Discussionmentioning
confidence: 94%
“…Eye-tracking studies have previously demonstrated that when viewing slides of models, men focus first and longest on faces compared with other body parts (Attard-Johnson & Bindemann, 2017; Hall et al, 2011; Nummenmaa et al, 2012). Gaze preference toward faces was also shown in men with pedophilia compared with healthy controls (Fromberger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation